2021
DOI: 10.1021/acs.chemmater.1c01500
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Multifunctional Metal Oxynitride 2D Crystals and Oriented Transparent Free-Standing Oxynitride Films

Abstract: Metal oxynitride two-dimensional (2D) crystals prepared by the delamination of layered compounds have attracted attention as photocatalysts, electrode catalysts, and electrolyte materials. However, the preparation of such materials is a significant challenge because of the difficulty related to producing chemically stable layered oxynitrides. In this study, oxynitride 2D crystals having triple perovskite units (A site: Ca, B site: Ta) were successfully prepared via the perfect delamination of the chemically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In previous literature, the Raman peak around 800 cm −1 was shown to correspond to one of the out-of-plane vibration modes of perovskite nanosheet layer in a layered perovskite. 27,42 Figure S17 shows another example of the comparison of Raman peaks at 700−850 cm −1 between the concave and convex sides of the free-standing BCTO nanosheet membrane. The peak also corresponded to the out-of-plane vibration of the perovskite layer and shifted slightly to higher wavenumbers for the convex side.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous literature, the Raman peak around 800 cm −1 was shown to correspond to one of the out-of-plane vibration modes of perovskite nanosheet layer in a layered perovskite. 27,42 Figure S17 shows another example of the comparison of Raman peaks at 700−850 cm −1 between the concave and convex sides of the free-standing BCTO nanosheet membrane. The peak also corresponded to the out-of-plane vibration of the perovskite layer and shifted slightly to higher wavenumbers for the convex side.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Several previous authors reported that free-standing membranes obtained by restacking monolayer nanosheets by spin-coating or vacuum filtration techniques showed excellent flexibility. Figure shows the cross-sectional SEM images and top-view photographs for the free-standing membranes fabricated by the vacuum filtration technique using BCTO, BSTO, and BNTO nanosheet dispersions. The SEM images showed the stacking structure of the membranes, which reflected face-to-face restacking of the nanosheets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sheets exhibited photocatalytic water splitting activity and were also able to transition to a free-standing film. 25 The present work demonstrates the interlayer modification and single layer exfoliation of the Ruddlesden–Popper oxynitride K 2 LaTa 2 O 6 N with the aim of obtaining high photocatalytic activity. K 2 LaTa 2 O 6 N, which has a structure comprising two-layer perovskite blocks, undergoes H + /K + exchange in water while maintaining a suitable degree of visible light absorption.…”
Section: Introductionmentioning
confidence: 93%
“…In particular, a mixed anion strategy to adjust the valence band by the preparation of semiconductors that include oxygen and other anion species has been investigated . To date, oxynitrides (O–N system), oxysulfides (O–S system), and oxyhalides (O–Cl, −Br, −I systems) , such as TaON, GaN:ZnO, Y 2 Ti 2 O 5 S 2 , Bi 4 NbO 8 Cl, and BiOBr have been reported. In these photocatalysts, anions such as N 3– , S 2– , and Cl – contribute to the formation of the orbitals at the top of the valence band, which results in a smaller bandgap than the corresponding oxides.…”
Section: Introductionmentioning
confidence: 99%